Analysis of the Rumen Microbiome and Metabolome to Study the Effect of an Antimethanogenic Treatment Applied in Early Life of Kid Goats - Abecia, Leticia; Martínez-Fernandez, Gonzalo; Waddams, Kate; Martín-García, Antonio Ignacio; Pinloche, Eric; Creevey, Christopher J.; Denman, Stuart Edward; Newbold, Charles James; Yáñez-Ruiz, David R. (Frontiers in Microbiology, 2018)
This work aimed to gain insight into the transition from milk to solid feeding at weaning combining genomics and metabolomics on rumen contents from goat kids treated with a methanogenic inhibitor (bromochloromethane, BCM). Sixteen goats giving birth to two kids were used. Eight does were treated (D+) with BCM after giving birth over 2 months. One kid per doe in both groups was treated with BCM (k+) for 3 months while the other untreated (k−). Rumen samples were collected from kids at weaning (W) and 1 (W+1) and 4 (W+4) months after and from does at weaning and subjected to 16S pyrosequencing and metabolomics analyses combining GC/LC-MS. Results from pyrosequencing showed a clear effect of age of kids, with more diverse bacterial community as solid feed becomes more important after weaning. A number of specific OTUs were significantly different as a result of BCM treatment of the kid at W while at W+1 and W+4 less OTUs were significantly changed. At W+1, Prevotella was increased and Butyrivibrio decreased in BCM treated kids. At W+4 only the effect of treating mothers resulted in significant changes in the abundance of some OTUs: Ruminococcus, Butyrivibrio and Prevotella. The analysis of the OTUs shared by different treatments revealed that kids at weaning had the largest number of unique OTUs compared with kids at W+1 (137), W+4 (238) and does (D) (23). D+k+ kids consistently shared more OTUs with mothers than the other three groups at the three sampling times. The metalobomic study identified 473 different metabolites. In does, lipid super pathway included the highest number of metabolites that were modified by BCM, while in kids all super-pathways were evenly affected. The metabolomic profile of samples from kids at W was different in composition as compared to W+1 and W+4, which may be directly ascribed to the process of rumen maturation and changes in the solid diet. This study shows the complexity of the bacterial community and metabolome in the rumen before weaning, which clearly differ from that after weaning and highlight the importance of the dam in transmitting the primary bacterial community after birth.